The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.19182/bft2015.325.a31270
|View full text |Cite
|
Sign up to set email alerts
|

La Végétation Des Inselbergs Du Sahel Burkinabè

Abstract: La végétation des inselbergs du Sahel burkinabèB o i s e t f o r ê t s d e s t r o p i q u e s , 2 0 1 5 , n° 3 2 5 ( 3 )Inselbergs are rocky outcrops characterised by the precarious nature of their edaphic and micro-climatic factors. The aim of this study was to compare the vegetation on inselbergs with the vegetation in the surrounding plains. The data were collected from 900 m 2 sampling plots in the woody stratum and 100 m 2 plots in the herbaceous stratum, by means of random stratified sampling. We conduc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
5
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 3 publications
2
5
0
1
Order By: Relevance
“…The dominance of Combretaceae (C. micranthum, C. glutinosum, C. nigricans, G. senegalensis and A. leiocarpa) highlighted in this study, and confirmed by post-drought floristic surveys in the Sudano-Sahelian region (Savadogo et al 2007, Bognounou et al 2009, Tindano et al 2015, Kusserow 2017, differs from the 1940s-1950s observations of Lavauden (1941) and Roberty (1946Roberty ( , 1954, which, in addition to the Combretaceae, noted the following as common species: A. ataxacantha, B. senegalensis, Diospyros mespiliformis, B. aegyptiaca, B. costatum, K. senegalensis, P. lucens, Sclerocarya birrea, T. indica and Terminalia avicennioides. The agroforestry parks were then almost all made up of trees in mixed stands dominated by V. paradoxa and P. biglobosa (Roberty 1946(Roberty , 1954.…”
Section: Environmental Conservationsupporting
confidence: 83%
“…The dominance of Combretaceae (C. micranthum, C. glutinosum, C. nigricans, G. senegalensis and A. leiocarpa) highlighted in this study, and confirmed by post-drought floristic surveys in the Sudano-Sahelian region (Savadogo et al 2007, Bognounou et al 2009, Tindano et al 2015, Kusserow 2017, differs from the 1940s-1950s observations of Lavauden (1941) and Roberty (1946Roberty ( , 1954, which, in addition to the Combretaceae, noted the following as common species: A. ataxacantha, B. senegalensis, Diospyros mespiliformis, B. aegyptiaca, B. costatum, K. senegalensis, P. lucens, Sclerocarya birrea, T. indica and Terminalia avicennioides. The agroforestry parks were then almost all made up of trees in mixed stands dominated by V. paradoxa and P. biglobosa (Roberty 1946(Roberty , 1954.…”
Section: Environmental Conservationsupporting
confidence: 83%
“…Plant community were collected in each phytogeographical sector using stratified and random sampling. Phytosociological surveys were carried out using the [ 23 ] method in plots of 30 m × 30 m (900 m 2 ) for the woody stratum [ 17 ] and 10 m × 10 m (100 m 2 ) for the herbaceous stratum [ 8 ]. For each survey, all observed species were listed, and each species was accompanied by its [ 23 ] abundance-dominance coefficient.…”
Section: Methodsmentioning
confidence: 99%
“…Inselbergs are characterized by their isolation from the surrounding relief and their independence from the regional hydrological network [ 5 , 6 ]. Inselbergs are distinct ecosystems due to the nature of their substrate, and vegetation [ 7 , 8 ]. Inselbergs are characterized by the presence of certain typical plant communities (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Floristic surveys were carried out on inselbergs and in their surroundings following stratified and random sampling. Data were collected in plots of 900 m² for the woody stratum and 100 m² for the herbaceous stratum (Kouassi et al, 2009;Tindano et al, 2015;Zerbo et al, 2017). The area of the plots in the micro-habitats of inselbergs varied from 0.25 m² to 9 m² depending on the size of the micro-habitat (Büdel et al, 1997;Porembski, 2000;Kouassi et al, 2014b).…”
Section: Sampling and Data Collectionmentioning
confidence: 99%